Socialization Process of Children in Piaget's and Vygotsky's Theories - Hasan Atak (Psikiyatride Güncel Yaklaşımlar, 2017)
Socialization is a process of being a society member. In this review, the process of socialization and views in several aspects of Piaget and Vygotsky about socialization are evaluated in respect of cultural structures. Piaget and Vygotsky are the most well-known theorists in the area of developmental psychology. While Vygotsky emphasizes the social basis during the period of cognitive development, Piaget is contented to explain the social basis with equilibrium concept. Vygotsky propounds that children interact with their social environment by their speech experiences so that they can learn, but Piaget claims that children actively become socialized and solve the problems that the social environment cause. Even though there are so many different explanations about the socialization between these two pioneers, the most notable difference can be represented that Piaget propounds that children become socialized while growing up, but Vygotsky claims that children become individuals while they growing up. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2017; 9(2.000): 163-176]